Evaluation of in vitro cytotoxic activity of mono-PEGylated StAP3 (Solanum tuberosum Aspartic Protease 3) forms - Muñoz, Fernando (2014)
StAP3 is a plant aspartic protease with cytotoxic activity toward a broad spectrum of pathogens, including potato and human pathogen microorganisms, and cancer cells, but not against human T cells, human red blood cells or plant cells. For this reason, StAP3 could be a promising and potential drug candidate for future therapies. In this work, the improvement of the performance of StAP3 was achieved by means of a modification with PEG. The separation of a mono-PEGylated StAP3 fraction was easily performed by gel filtration chromatography. The mono-PEGylated StAP3 fraction was studied in terms of in vitro antimicrobial activity, exhibiting higher antimicrobial activity against Fusarium solani spores and Bacillus cereus, but slightly lower activity against Escherichia coli than native protein. Such increase in antifungal activity has not been reported previously for a PEGylated plant protein. In addition, PEGylation did not affect the selective cytotoxicity of StAP3, since no hemolytic activity was observed.